Effect of salinity on the survival and growth of mud crabling, Scylla serrata (University Journal of Zoology, Rajshahi University, 2012)
An experiment was conducted for a period of eight weeks under laboratory conditions to determine the effect of different salinity levels on the survival and growth of crablings of mud crab, Scylla serrata. The different salinity levels tested were: 5 ppt, 10 ppt, 15 ppt, 20 ppt and 25 ppt. The differences in growth increment in terms of body weight (BW) were significant (p